TEACHER'S INTERPERSONAL COMMUNICATION SKILL TOWARD STUDENTS WITH SPECIAL NEEDS - Barida, Muya; Widyastuti, Dian Ari (International Journal of Psychosocial Rehabilitation, 2020)
Regular students are characterized with average ability or above-average ability, while students with special needs refer to those who are below the average (slow learner, students with intellectual disability). The current study is aimed at finding out the difference of elementary school teacher's interpersonal communication skill toward regular students and students categorized as slow learner/ students with intellectual disability. This study proposed a hypothesis stating that there is no difference in teacher's interpersonal communication skill toward regular students and toward students with special needs. This study employed descriptive survey with descriptive comparative study design. The subject of the study was fifty teachers from 19 elementary schools who were selected through simple random sampling. The collected data were in the form of communication skill obtained from Interpersonal Communication Skill Scale. The data were then analyzed using T-test. The analysis resulted in sig. 0.165 (>0.05), thus it could be concluded that the null hypothesis (Ho) was accepted. In other words, there is no difference in teacher's interpersonal communication skill between regular students and students categorized as slow learner/students with intellectual disability of elementary school in Sukoharjo Regency, Central Java Province.